Training propensity of start-ups in Switzerland : a study based on data for the start-up cohort 1996-97 - Arvanitis, Spyros [Verfasser]; Stucki, Tobias [Verfasser] (My University, 2008)
"This study is based on data a cohort of Swiss firms that were founded in 1996/97. In the year 2000 data were collected by means of a postal survey among those firms, which still existed by that time. In 2003 and 2006 two further surveys were conducted among the participants of the respective last study. In this study we analyzed, firstly, the determinants of the propensity to train apprentices of new firms and how they change with increasing firm age. Secondly, we investigated how a firm's training propensity correlated with its labour productivity. To this end, we specified an equation for training propensity and an equation for labour productivity, which included as an additional production factor the endogenized propensity to train apprentices." (Autorenreferat, BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; S 1.3 Berufliche Erstausbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2.1 Westeuropa; Unternehmensgründung; Betriebliche Berufsausbildung; Ausbildungsbereitschaft; Einflussfaktor; Korrelation; Produktivität; Kosten-Nutzen-Relation; Schweiz